Fractional action cosmology with an effective \(\wedge\) -term - Shchigolev, Victor (International Journal of Advanced Astronomy, 2016)
We continue studying the cosmological models derived from the fractional variational principle applied to the gravitational sector of the action functional. Within the frame of these models, the effective cosmological term could arise as a result of the non-zero Hubble parameter. At the same time, the continuity equation for the matter remains unchanged in its standard form. In this work, we are going to obtain some exact solutions for our model originating from the several kinematic assumptions. At that, we find the main cosmography parameters of the model and the corresponding equations of state of matter that fills the universe se. First, we proceed from an initially given law of evolution of the universe in some standard scenarios. Then, several exact solutions are obtained from the proposed earlier evolutionary laws for the effective cosmological term.